Challenges in Discord Application Among Quantity Surveying Students - Mazura, Mahdzir; Nik Fatma Arisya, Nik Yahya; Zetty, Pakir Mastan; Lai, Min Yuet; Nafisah, Ya'cob@Ya'acob (INTI International University, 2023)
The global epidemic continues to have a significant impact on the world due to the recent and unexpected COVID-19 pandemic. Even the education industry has been severely disrupted and affected. All universities have been forced to change their learning methods from face-to-face to e-learning. Hence, it is necessary to utilize technological aids such as Discord as it can naturally capture the attention of students. On top of that, the features of Discord, especially the integration of text chat, voice call and screen sharing can fulfil most of the students’ requirements during online learning. This paper aims to explore the challenges associated with the Discord application among QS students. Through the use of a quantitative method, a set of questionnaires is distributed to the TARUMT students enrolled in the Quantity Surveying course (year 1 to year 4). Out of 200 questionnaires, 87 responses have been received and were analyzed using frequency statistics, Cronbach’s Alpha analysis, and Descriptive analysis. The results revealed several challenges, including limitation of upload size, disconnected discord application, random audio cut offs, privacy issues and engaging in harassment. In conclusion, the results identified the most and the least significant issues that may affect students' use of Discord applications. This data is valuable in shaping appropriate strategies for Quantity Surveying education.